Decision-making in septal deviations: Septoplasty for anterior septal deviations and submucosal resection for posterior deviations: Is it a practical method? - Rathod Sunil Kumar; Harish Swamy Dharmagadda; Kathyayani Burugula (Advances in Human Biology, 2023)
Introduction: Classification of septal deviations is varied, but their application in selecting the type of septal surgery is not decisive. Classifying the septal deviations and using it to decide the choice of surgery was reviewed. The aim of the study is to review the use of classification of septal deviations into anterior and posterior to select septoplasty and submucosal resection (SMR), respectively. Materials and Methods: Thirty-four patients with anterior deviated nasal septum were grouped as Group A. Another 34 patients with posterior septal deviation were grouped as Group B. In Group A, patients were aged between 18 years and 47 years with a mean age of 34.28 ± 2.30 years. In Group B, they were aged between 19 and 48 years, with a mean age of 35.25 ± 3.05 years. The male-to-female ratio of the total 68 patients was 1.4:1. Nasal obstruction symptom evaluation (NOSE) score Grade 4 and 5 was noted in 31 (45.48%) patients in Group A and 33 (48.52%) patients in Group B. Right side deviation was noted in 15 (22.05%) of the Group A patients and 20 (29.41%) of the Group B patients. Results: All patients with anterior deviation were subjected to septoplasty, and patients with posterior deviation were subjected to classical SMR surgery. The results were assessed and analysed using the response of recovery in the nasal obstruction NOSE score and the two groups were correlated using Pearson's Correlation coefficient calculator. The R score was 0.9942, and the P value was 0.0001 (P taken as significant at < 0.05). Conclusion: It was observed by the results that deciding the type of surgery as per the direct nasal endoscopy findings whether it was anterior or posterior deviation was easy, practical, and definite final outcome results could be expected at the end.